Synnema triflorum (Roxb. ex Nees) O. Kuntze.- a New Record for Upper Gangetic Plain - Dixit, S. N.; Singh, S. K. (Indian Forester, 1968)
This note presents Synnema triflorum (Roxb. ex Nees) O. Kuntze, as a new record for Upper Gangetic Plain and furnishes important informations regarding its habit, habitat, exact localities of occurrence and frequency in the area.